Effect of pH on the adsorption kinetics of Cr(VI) on sodium chlorite treated coconut coir - Islam, MN; Ahmed, N; Hossain, MY; Rahman, AKML; Sultana, A (Bangladesh Journal of Scientific and Industrial Research, 2016)
Coconut coir is a low cost bioadsorbent containing large amount of lignin. In this research work sodium chlorite treated coconut coir (SCT CC) was used to remove Cr(VI) from industrial wastewater by implementing adsorption technique through the investigation of the adsorption kinetics at different pH values. The maximum Cr(VI) adsorption capacity of SCT-CC at pH 2.00, 3.00, 5.00 and 7.00 was 24.75, 23.92, 16.07 and 6.31 mg Cr(VI) g-1 SCT-CC respectively with the dose of 7.5 g/L. The equilibrium established within three hours resulting the maximum removal (95%) of chromium. The adsorption kinetics of Cr(VI) on SCT-CC was found to be regulated by pH of the system. Rate of adsorption was the highest at pH 2.00 and the kinetic data well-fitted with Ho's pseudo second order kinetics. Fourier transform infrared (FT-IR) spectrometry analysis indicated that the carbonyl (C=O) groups and hydroxy (O-H) groups from the lignin structure in coconut coir may be involved in the mechanism of Cr(VI) adsorption and it showed good agreement with the kinetic data to elucidate the adsorption mechanism Bangladesh J. Sci. Ind. Res. 51(2), 95-100, 2016